Moving forward in implementing green infrastructures: Stakeholder perceptions of opportunities and obstacles in a major North American metropolitan area. (November 2018) - Bissonnette, Jean-François; Dupras, Jérôme; Messier, Christian; Lechowicz, Martin; Dagenais, Danielle; Paquette, Alain; Jaeger, Jochen A.G.; Gonzalez, Andrew
Abstract: Urbanization poses both challenges and opportunities for the management of urban ecosystems globally. In the Greater Montreal Area (GMA), a major North American urban area where green infrastructure (GI) implementation is in its early stage, there are challenges in maintaining provision of ecosystem services due to urban expansion and climate change impacts. In response, stakeholders in the GMA are trying to further integrate the GI concept into planning practices and have participated in focus groups to discuss various approaches to implementing the GI concept. This paper addresses stakeholder perceptions of the opportunities and obstacles related to natural ecosystem management in the GMA. We discuss the way in which participants perceive the prospect of the GI concept to influence discourse and policy about environmental planning. We found plural perspectives on GI yet there was a broad consensus regarding problems in bringing planning tools in line with socio-ecological processes. This research provides a novel contribution by showing how the concept of GI informs narratives about metropolitan green space and environmental planning. The narratives of most research participants emphasised: 1) that efforts to protect and enhance the urban ecosystem should be approached within a coherent social and ecological framework at the scale of the metropolitan area, and 2) that GI planning needed to rely on collaborative and participatory approaches to enhance ecosystem services at all scales of the GMA. Highlights: GI provides a comprehensive approach to urban environmental planning, and is conducive to identifying limitations in existing policies. Moving forward with GI implementation requires planing approaches integrating diverse sources of knowledge through public participation. Discussions about GI raises a normative dimension about interactions between socioecological processes and structures of governance. Narratives on GI emphasise the importance of distributing benefits and costs related to ecosystem management through improved collaboration. The adaptability of the GI concept constitutes an impediment to persuade central actors to implement a coherent regional scale approach.